Sosialisasi Dampak Penggunaan Gadget terhadap Anak di Desa Timbang Lawan - Reflina Reflina; Elsa Nandita; Irmayati Khairiyah; Dea Putri Ananda Mahela; Meylia Hapni Tanjung (Fakultas Teknik Universitas Cenderawasih, 2024)
Technology, especially gadgets, has evolved rapidly and become an integral part of our everyday life. The widespread use of gadgets, especially among children, brings significant positive and negative impacts. This research aims to socialize the impact of gadget use on children in the Timbang Lawan Village, Langkat Regency. This socialization program is designed toprovide information to the community about the effects of gadget use, both positive and negative, as well as ways to overcome these negative impacts. both positive and negative, as well as ways to overcome these negative impacts. Methods The research method used was descriptive observational, which involved data collection, classification, analysis, and report generation. Results socialization showed that excessive use of gadgets can result in negative impacts such as addiction, decreased social skills,as well as interference in learning. Conversely, positive impacts include ease of communication, increased creativity, and faster access to information. faster access to information. Through this socialization program, it is hoped that the community, especially parents, can better understand and manage the use of gadgets in children.parents, can better understand and manage the use of gadgets in their children their children. Recommendations include time restrictions on gadget use and stricter supervision to prevent negative impacts and utilize the positive benefits of this technology the positive benefits of this technology.